PERAN GURU PEMBIMBING DALAM KESIAPAN KERJA SISWA KELAS X SMK NEGERI 2 SAWAHLUNTO SUMATERA BARAT - Mirna Ari Mulyani (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2012)
Based on preliminary observations, it was observed that most of the supervising teachers have not been optimal in helping to improve the capabilities, potential, talents, interests, personality and achievements, especially in the students’ work readiness. This study was aimed describe the role of supervising teachers in improving 10thgrade students’ readiness to work at SMK Negeri 2 Sawahlunto, West Sumatra. The methods and types of this research is descriptive quantitative. The findings of this study is the role of the guidance counselor in job readiness 10th grade student SMK Negeri 2 Sawahlunto West Sumatra is very high category in helping students understand themselves, know about job opportunities, developing a positive attitude towards work. Based on the findings, it can be concluded that the importance of the role of the guidance counselor in vocational students job readiness 10th grade students. This study implies that more attention in developing programs in the field of career guidance in vocational schools in order to improve the readiness of the student's work. For further research, it is recommended to study other aspects that contribute to the quality of work students’ for 10th grade students.